Biodegradable Polystyrene doped with N-Benzyl-4-Vinylpyridinium Chloride for Bio-Sensor Device Applications - Abdullah Hasan Jabbar (Journal of Global Pharma Technology, 2018)
Waste polymers are recently getting higher research interest and one of the solutions is synthesizing synthetic biodegradable polymers where the focus is to modify polymer chemical structure without altering its intended application. Biodegradation of polystyrene is one of the major research concern and is extremely difficult to accommodate the best physical, chemical and optical properties of the desired polystyrene end products. Doping polystyrene with copolymer such as N-benzyl-4-vinyl pyridinium chloride, PSt-co-BVP(Cl), has been found able to be bio-degradable when treated with activated sludge in the soil. The biodegradation of polystyrene copolymer that contained 46.1-mol % BVP(C1) is found to follow first-order kinetic and with a half-life of 5.5 days when about 0.5 or 1.0 g/kg of polystyrene is utilized as basic materials. Polymeric base materials have gained a wide theoretical interest and practical application in sensor technology which motivated this research in finding ways to modify the PSt-co-BVP(Cl) and investigate its chemical structure modification by low dose laser irradiation. The laser photon modifies PSt-co-BVP(Cl) of its physical, chemical and surface morphology where the strong oncoming of BVP(Cl) with microbial cells and viruses can be tuned as bio-materials sensor.